Concept For a System to Evaluate the Innovative Capability of Small and Medium-Sized Enterprises - Witold ZYCH; Karolina CHRABĄSZCZ – SARAD (Communications of International Proceedings, 2021)
The aim of the article is to present the concept of evaluation of innovative capability of an enterprise and to present the results of empirical research, i.e. to determine the degree of innovative capability of two enterprises of the SME sector. The main problem presented in the article is to identify the innovation capability gap, which is the difference between the desired and the possessed innovation potential of an enterprise. A set of key determinants of innovative capability, constituting the basis for a system of evaluation of this capability, has been identified during two-phase own research. In the case described in this article, 13 evaluation criteria were adopted, to which appropriate weights and evaluation scales were assigned, and then a model for the evaluation of an enterprise's innovative capability was presented. In the empirical part of the article, the concept of innovative capability was verified and the results of empirical research was presented in the Charter of innovative capability of enterprises. The main determinants and, at the same time, the criterion for assessing the development of innovative capability are managerial and employee competencies in innovation, cooperation with customers and business partners in the area of knowledge, teamwork and pro-innovative organisational culture, modernity of IT infrastructure. A sequence of actions aimed at bridging the innovation potential gap and stimulating the course of innovation processes in the surveyed SMEs was given. The ability to analyze and improve the knowledge and innovation management process determines the future of an oganisation.
Keywords: Innovation; Innovative Capability; Evaluation of Innovative Capability; SME Enterprises